P.2.10 Healthcare provider communication and the duration of time off work among injured workers: a prospective cohort study. (April 2019) - Lane, Tyler; Lilley, Rebbecca; Black, Ollie; Sim, Malcolm; Smith, Peter
Abstract : Background: In addition to biomedical treatment, healthcare providers (HCPs) may make psychosocial contributions to injured workers that aide rehabilitation and the return to work (RTW) process. We examined the effect on disability duration of several types of HCP communications with injured workers and stakeholders in the RTW process. Objectives: To test the effect of various HCP communications on time off work following injury. Research design: We analysed survey and administrative claims data from n=715 injured workers in Victoria, Australia. Survey responses were collected around five months post-injury and provided data on HCP communication and confounders. Administrative claims data provided data on compensated time off work. We conducted multivariate zero-inflated Poisson regression analyses, which evaluated both the likelihood of future time off work and its duration. Measures: HCP communications included good interactions, estimated RTW date, activity discussions, prevention discussions, and stakeholder contact. Time off work was the count of cumulative compensated work absence in weeks, accrued post-survey. Results: Only RTW dates were predictive of no future time loss (OR: 2.65, 95% CI: 1.74–4.03). RTW date (IRR: 0.71, 0.67–0.74), good interactions (IRR: 0.73, 0.70–0.76), and stakeholder contact (IRR: 0.92, 0.88–0.95) reduced time off work, while activity discussions predicted more time off work (IRR: 1.13, 1.08–1.19). Conclusions: HCPs may be able shorten disability durations through several types of communication. Of those evaluated in this study, RTW dates had the most robust effect.